EWaS5 International Conference: &Amp;ldquo;Water Security and Safety Management: Emerging Threats or New Challenges? Moving Fro 2022
DOI: 10.3390/environsciproc2022021038
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of an IoT Device for Measuring Discharges in Sanitation Networks

Abstract: This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https:// creativecommons.org/licenses/by/ 4.0/).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…These studies employed varying levels of experimentation, validation, and reliability testing to assess the accuracy and reliability of sensor readings [58], [98], [109], [110]. For example, Jeffery et al [111] conducted laboratory and field tests to evaluate the performance of water level sensors, while Pérez-Padillo et al [112] tested sensors in the field at a wastewater treatment plant, where the device was installed in a spillway. The authors found that sensors can accurately measure the occurrence, duration, and water level during discharge episodes.…”
Section: ) Sensors and Sensing Technologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies employed varying levels of experimentation, validation, and reliability testing to assess the accuracy and reliability of sensor readings [58], [98], [109], [110]. For example, Jeffery et al [111] conducted laboratory and field tests to evaluate the performance of water level sensors, while Pérez-Padillo et al [112] tested sensors in the field at a wastewater treatment plant, where the device was installed in a spillway. The authors found that sensors can accurately measure the occurrence, duration, and water level during discharge episodes.…”
Section: ) Sensors and Sensing Technologiesmentioning
confidence: 99%
“…These benefits include improved water quality [96], [101], ecosystem tracking [113], reduction in solid waste [114], reduction in potable water consumption for irrigation [104], and optimization of water resources [58]. Similarly, cost reduction and improved efficiency were mentioned in six papers, including those by Praveena et al [102], Jeffery et al [111], Latif et al [100], Sasirekha et al [116], Alshami et al [109], and Pérez-Padillo et al [112]. These studies suggested that IoT-based wastewater infrastructure management can significantly decrease operational costs and enhance overall efficiency, leading to better resource utilization and cost savings.…”
Section: ) Sensors and Sensing Technologiesmentioning
confidence: 99%
See 1 more Smart Citation